(untitled) (Colombia Medica, 2010)
Objective: Malaria infection is severe in children who are believed to be more at risk because of their relative poor immunity against the disease. Some cytokine levels (IFN-g, IL-2, IL-4, and IL-10) of children, adolescents, and adults were assessed in this study. Methods: Cytokine levels were assayed by using Enzyme Linked Immunosorbent Assay (ELISA). Malaria diagnosis and blood parameters were carried out by using standard parasitological and haematological techniques. Results: The mean cytokine levels were significantly elevated in children, adolescent, and adult subjects when compared to their respective healthy controls (p